PENGUJIAN KUALITAS AIR BERSIH DI PERMUKIMAN MASYARAKAT DESA GUDANG, KECAMATAN TANJUNGSARI, JAWA BARAT - Fanny Novia; Cahyana, Gede H; Mulyani, Tri; Febrion, Churchil; Muchamad, Arief Nur; Susanto, Arif; Herliana, Erika; Heryadi, Gumelar Aditya; Azzahra Putri W, Keysha Alfatthya (JURNAL PENGABDIAN KEPADA MASYARAKAT (JPKM) KEBANGSAAN, 2025)
Gudang Village is one of the villages in Tanjung Sari District, Sumedang Regency, West Java that uses groundwater as source of clean water. The Community Service activity aims to deliver introduction about clean water quality standard and also to conduct groundwater quality testing in community housing. Results showed temperature and total dissolved solid (TDS) parameters still meet the quality standard. Meanwhile, 35,29% of groundwater visual looks turbid and smelly. The pH value of groundwater showed about 88,24% of groundwater has pH value <6.5. In general, groundwater in Desa Gudang are safe as source of clean water